Finite-approximate controllability of semilinear fractional stochastic integro-differential equations - Mahmudov, N., I (Pergamon-Elsevier Science Ltd, 2020)
We introduce the concepts of simultaneous finite dimensional exact and mean square approximate controllability (finite-approximate controllability) in the framework of semilinear fractional stochastic integro-differential evolution Ito equations. Under the approximate controllability of the corresponding linear part we obtain sufficient conditions for the finite-approximate controllability of the semilinear fractional stochastic integro-differential evolution equation. At the end, an example of stochastic heat equation is given to show applicability of our result. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Finite-approximate controllability; Approximate controllability; Stochastic evolution equation